HLA-DR and HLA-DP genotypes and immunoglobulin E responses to common major allergens. - Young, R; Dekker, J; Wordsworth, B; Schou, C; Pile, K; Matthiesen, F; Rosenberg, WM; Bell, J; Hopkin, J; Cookson, W (1994)
In order to test for human histocompatibility leucocyte antigens (HLA) class II restriction of IgE responses, 431 subjects from 83 families were genotyped at the HLA-DR and HLA-DP loci and serotyped for IgE responses to six major allergens from common aero-allergen sources. A possible excess of HLA-DR1 was found in subjects who were responsive to Fel d I compared with those who were not (Odds Ratio (OR) = 2, P = 0.002), and a possible excess of HLA-DR4 was found in subjects responsive to Alt a I (OR = 1.9, P = 0.006). Increased sharing of HLA-DR/DP haplotypes was seen in sibling pairs responding to both allergens. Der p I, Der p II, Phl p V and Can f I were not associated with any definite excess of HLA-DR alleles. No significant correlations were seen with HLA-DP genotype and reactivity to any of the allergens. The results suggest class II HLA restriction is insufficient to account for individual differences in reactivity to common allergens.